Impact of synchronous metastasis distribution on cancer specific survival in renal cell carcinoma after radical nephrectomy with tumor thrombectomy - Tilki, Derya; Hohenfellner, Markus; Pahernik, Sascha (The journal of urology, 2015)
Purpose: - Metastatic renal cell carcinoma can be clinically diverse in terms of the pattern - of metastatic disease and response to treatment. We studied the impact of metastasis - and location on cancer specific survival. - Materials and Methods: - The records of 2,017 patients with renal cell cancer and tumor thrombus who underwent - radical nephrectomy and tumor thrombectomy from 1971 to 2012 at 22 centers in the - United States and Europe were analyzed. Number and location of synchronous metastases - were compared with respect to patient cancer specific survival. Multivariable Cox - regression models were used to quantify the impact of covariates. - Results: - Lymph node metastasis (155) or distant metastasis (725) was present in 880 (44%) patients. - Of the patients with distant disease 385 (53%) had an isolated metastasis. The 5-year - cancer specific survival was 51.3% (95% CI 48.6-53.9) for the entire group. On univariable - analysis patients with isolated lymph node metastasis had a significantly worse cancer - specific survival than those with a solitary distant metastasis. The location of distant - metastasis did not have any significant effect on cancer specific survival. On multivariable - analysis the presence of lymph node metastasis, isolated distant metastasis and multiple - distant metastases were independently associated with cancer specific survival. Moreover - higher tumor thrombus level, papillary histology and the use of postoperative systemic - therapy were independently associated with worse cancer specific survival. - Conclusions: - In our multi-institutional series of patients with renal cell cancer who underwent -radical nephrectomy and tumor thrombectomy, almost half of the patients had synchronous - lymph node or distant organ metastasis. Survival was superior in patients with solitary - distant metastasis compared to isolated lymph node disease.
Gesehen am 02.07.2020